2021
DOI: 10.1109/access.2021.3100410
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Assessment of Business Intelligence System Adoption Model for Sustainable Textile and Apparel Industry

Abstract: The textile and apparel industry is one of the biggest competitive industries in the world. Nowadays, industry 4.0 concepts put pressures on textile and apparel companies to integrate advanced technologies. Consequently, Business Intelligence (BI) systems are diffusing rapidly to process large data sets to harness the true value of smart technologies. Regardless of its potentials, most textile and apparel companies are lagging and hesitating to adopt this credible innovation in the presence of a high failure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Without the talents and knowledge of patternmakers, ready-to-wear apparel would not be possible in the clothing or fashion design industries. Today, the textile and apparel industries have created numerous job opportunities in a variety of fields, including fabric or dressmakers (for whom pattern making is a strength), textile cutting machine operators or machinists, fashion illustrators, fashion merchandize, patternmakers or designers, and clothing maintenance (Ahmad et al, 2021). The fact that the patterns they develop serve as the foundation on which the finished clothing is made makes clothing pattern makers essential to the fashion and apparel industries.…”
Section: Teaching and Learning Of Pattern Drafting At The Tertiary Levelmentioning
confidence: 99%
“…Without the talents and knowledge of patternmakers, ready-to-wear apparel would not be possible in the clothing or fashion design industries. Today, the textile and apparel industries have created numerous job opportunities in a variety of fields, including fabric or dressmakers (for whom pattern making is a strength), textile cutting machine operators or machinists, fashion illustrators, fashion merchandize, patternmakers or designers, and clothing maintenance (Ahmad et al, 2021). The fact that the patterns they develop serve as the foundation on which the finished clothing is made makes clothing pattern makers essential to the fashion and apparel industries.…”
Section: Teaching and Learning Of Pattern Drafting At The Tertiary Levelmentioning
confidence: 99%
“…For example, Apple's failure to use BI efficiency in optimizing its customer service and late shipping its products to its retailers, and KFC closed branches as it failed to duly manage and proceed with supply chain-relevant information using data analytics. Likewise, Ahmad et al (2021) estimated that 80% of BI projects fail in emerging economies. Emerging economies, also called emerging markets such as Jordan, have some IT infrastructure similarities to developed countries, but are still not yet fully developed (Al-Okaily and Al-Okaily, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that 70 to 85% of BIS projects fail to yield the expected returns (Trieu, 2022; Ain et al , 2019). In emerging economies, Ahmad et al (2021) estimated a failure rate of about 80% due to both technological and managerial issues. In Jordan, many organizations are not able to make BIS an effective tool for decision making, thereby failing to create a competitive advantage, and its success is questionable (Al-Okaily et al , 2022a; Masa’Deh et al , 2021; Al-Okaily et al , 2021a).…”
Section: Introductionmentioning
confidence: 99%